Modelling technique of the object-attribute system oriented to data mining. (2018) - Hu, Yaoyu; Wang, Ai
The research of modelling the object-attribute system, essentially a two dimensional problem, belongs to the domain of interpretative structural modelling and it is one of the basic problems in the data mining field. Firstly, this paper proposes and demonstrates the subsystem judgement theorem. In order to solve the problem above, this paper puts forward an algorithm which can reduce the scale and the dimension of the original data through modelling the object-attribute system based on the object similar feature matrix (OSFM). In the last part of the paper, a numerical value example is provided to show the whole process of the method.